Functional and compositional characterization of galiang (Cystosperma merkusii) - Lopez, Ma. Isabela A.; Dumelod, Benelyn Domingo (1999.)
The research was conducted to assess the functional properties and proximate composition of galiang flour and determine what food products may be made from it. A preliminary study was also done which included the determination of the crude protein content of galiang flour and the determination of gelling point of galiang flour . The former was done to know if both protein-related and carbohydrate-related functional characteristics were to be assessed; and the latter was essential in determining which temperatures were to be used in the viscosity test. All the results of the experiments were compared with all-purpose flour. Phase I (Assessment of the Functional Properties of Galiang Flour) showed that galiang flour dissolves at a low pH as opposed to all-purpose flour that requires a higher pH value for dissolution. The water-absorption, viscosity, fat-absorption properties of galiang flour were greated than those of the all-purpose flour. Galiang flour gels at a lower concentration (3%) than all-purpose flour (12%). As for the doughing properties, galiang flour is able to form dough but lacks the elasticity that all-purpose flour exhibits. The bulk densities of galiang flour and all-purpose flour showed no difference at all. Phase II (Proximate analysis) showed that galiang flour contains more moisture, crude fiber and ash than all-purposed flour but its crude protein and crude fat are much less than those of all-purpose flour. The available carbohydrate contents of the flour samples are almost at par with each other.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Galiang -- Composition